Membentuk Jati Diri Remaja Yang Kuat : Cipta, Rasa, Karsa dan Pengendalian Diri - Edy Soesanto; Eka Eka (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The formation of a strong identity is a complex process involving the harmonisation of cognitive, affective and conative aspects within the individual. This research aims to examine how the concept of ‘cipta, rasa, karsa, and self-control’ in Javanese philosophy can be a relevant framework in building a strong identity in the modern era. Through literature study and qualitative analysis, this research reveals that ‘cipta’ refers to the ability to think critically and creatively, ‘rasa’ is related to emotional intelligence and empathy, ‘karsa’ refers to the will and goal-oriented actions, and ‘self-control’ relates to the ability to regulate emotions, thoughts, and behaviour. These four aspects are interrelated and mutually reinforcing in forming the foundation of a strong identity. The results of the study show that the integration of creation, rasa, karsa, and self-control can equip individuals with high adaptability, strong resilience, and solid moral values. Individuals with a strong identity tend to have clear life goals, are able to make wise decisions, and are able to establish positive social relationships. This research also highlights the importance of cultural context in the formation of identity. The concept of ‘cipta, rasa, karsa, and self-control’ derived from Javanese philosophy can provide a unique and relevant perspective for Indonesian society. However, further adaptation and development is needed so that this concept can be effectively implemented in the context of modern life.